Estimates of global, regional, and national morbidity, mortality, and aetiologies of diarrhoeal diseases: a systematic analysis for the Global Burden of Disease Study 2015. Issue 9 (September 2017) - ; Troeger, Christopher; Forouzanfar, Mohammad; Rao, Puja C; Khalil, Ibrahim; Brown, Alexandria; Reiner, Robert C; Fullman, Nancy; Thompson, Robert L; Abajobir, Amanuel; Ahmed, Muktar; Alemayohu, Mulubirhan Assefa; et al.
Summary: Background: The Global Burden of Diseases, Injuries, and Risk Factors Study 2015 (GBD 2015) provides an up-to-date analysis of the burden of diarrhoeal diseases. This study assesses cases, deaths, and aetiologies spanning the past 25 years and informs the changing picture of diarrhoeal disease worldwide. Methods: We estimated diarrhoeal mortality by age, sex, geography, and year using the Cause of Death Ensemble Model (CODEm), a modelling platform shared across most causes of death in the GBD 2015 study. We modelled diarrhoeal morbidity, including incidence and prevalence, using a meta-regression platform called DisMod-MR. We estimated aetiologies for diarrhoeal diseases using a counterfactual approach that incorporates the aetiology-specific risk of diarrhoeal disease and the prevalence of the aetiology in diarrhoea episodes. We used the Socio-demographic Index, a summary indicator derived from measures of income per capita, educational attainment, and fertility, to assess trends in diarrhoeal mortality. The two leading risk factors for diarrhoea—childhood malnutrition and unsafe water, sanitation, and hygiene—were used in a decomposition analysis to establish the relative contribution of changes in diarrhoea disability-adjusted life-years (DALYs). Findings: Globally, in 2015, we estimate that diarrhoea was a leading cause of death among all ages (1·31 million deaths, 95% uncertainty interval [95% UI] 1·23 million to 1·39 million), as well as a leading cause of DALYs because of its disproportionate impact on young children (71·59 million DALYs, 66·44 million to 77·21 million). Diarrhoea was a common cause of death among children under 5 years old (499 000 deaths, 95% UI 447 000–558 000). The number of deaths due to diarrhoea decreased by an estimated 20·8% (95% UI 15·4–26·1) from 2005 to 2015. Rotavirus was the leading cause of diarrhoea deaths (199 000, 95% UI 165 000–241 000), followed by Shigella spp (164 300, 85 000–278 700) and Salmonella spp (90 300, 95% UI 34 100–183 100). Among children under 5 years old, the three aetiologies responsible for the most deaths were rotavirus, Cryptosporidium spp, and Shigella spp. Improvements in safe water and sanitation have decreased diarrhoeal DALYs by 13·4%, and reductions in childhood undernutrition have decreased diarrhoeal DALYs by 10·0% between 2005 and 2015. Interpretation: At the global level, deaths due to diarrhoeal diseases have decreased substantially in the past 25 years, although progress has been faster in some countries than others. Diarrhoea remains a largely preventable disease and cause of death, and continued efforts to improve access to safe water, sanitation, and childhood nutrition will be important in reducing the global burden of diarrhoea. Funding: Bill & Melinda Gates Foundation.